2017
DOI: 10.1007/s11661-017-4117-7
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Grain Refinement of Additive-Manufactured Ti-xW Alloys

Abstract: It is necessary to better understand the composition-processing-microstructure relationships that exist for materials produced by additive manufacturing. To this end, Laser Engineered Net Shaping (LENSä), a type of additive manufacturing, was used to produce a compositionally graded titanium binary model alloy system (Ti-xW specimen (0 £ x £ 30 wt pct), so that relationships could be made between composition, processing, and the prior beta grain size. Importantly, the thermophysical properties of the Ti-xW, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 40 publications
0
31
1
Order By: Relevance
“…In alloys such as Ti-6Al-4 V, which has a very narrow freezing range, such epitaxial growth is quite common. In other alloys where it is possible to further undercool the liquid or promote nucleation, it is possible to develop equiaxed grain structures [40,41]. These results suggest that Ni may also be suitable for promoting equiaxed grains, although the precise solidification details (e.g., Marangoni convection, undercooling, growth restriction [42]) have not been established.…”
Section: Application To Ti-ni Alloys High Throughput Processingmentioning
confidence: 99%
“…In alloys such as Ti-6Al-4 V, which has a very narrow freezing range, such epitaxial growth is quite common. In other alloys where it is possible to further undercool the liquid or promote nucleation, it is possible to develop equiaxed grain structures [40,41]. These results suggest that Ni may also be suitable for promoting equiaxed grains, although the precise solidification details (e.g., Marangoni convection, undercooling, growth restriction [42]) have not been established.…”
Section: Application To Ti-ni Alloys High Throughput Processingmentioning
confidence: 99%
“…The simulated concentration fluctuations can be compared to experimental data of the concentration variation of W collected by EDS, as described in Mendoza et al [63] and shown in Figure 11(b). The experimental concentration profile showed variations in solute concentration with periodicity that is quite close to what we predict in the simulations (about 7 µm).…”
Section: Comparison To Experimentsmentioning
confidence: 99%
“…[63] We employed the commercial software package COMSOL Multiphysics ® to model the macroscale process as a simplified beam melting problem, considering the effects of fluid flow, heat transport, and temperature-dependent materials properties. At the microscale, information passed from COMSOL simulations is used to determine initial conditions, thermal gradients, cooling rates, and fluid flow velocities to be passed to a LB-CA model.…”
Section: The Laser Engineered Net Shaping (Lens™)mentioning
confidence: 99%
See 1 more Smart Citation
“…Once entrained in the liquid, the melt pool dynamics are equally complex, with Marangoni convection, evaporation, wetting and capillarity playing strong roles (among many other operating physics). The liquid metal velocity is quite high, and results in features that resemble comet tails as melting particles leave molten material behind them as they move through the molten pool (Mendoza et al, 2017). These physics present challenges in understanding and modelling AM processes, but it is expected that over the next three to five years, a number of research groups will be able to contribute to the knowledgebase of the heat source/particle interactions.…”
Section: Powder-based Additive Manufacturing Processesmentioning
confidence: 99%